KOMO TUNA FISHING EFFORT (Euthynnus affinis) IN THE ARCHIPELAGO FISHERY PORT OF SIBOLGA NORTH - Demiria Simanjuntak; Pareng Rengi; Usman Usman (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2020)
ABSTRACTThe aim of this research is to determine the business units of Komo tuna fishing (Euthynnus affinis) that are suitable to be developed and continued for purse seine and gillnet fishing gear based on biological, technical, social and economic aspects. The method used in this study is a survey method, aiming to get a picture of the object under study, conducted with interviews with fishermen purse seine and gillnet fishing gear. Data analysis using scoring analysis. The results of a combined analysis of biological, technical, social and economic aspects show that the value of the VA purse seine function has the same value as a gillnet fishing gear which is 2.00. Thus the two fishing gear are worth continuing and developing.Keywords: fishing gear, fishing business, kawa-kawa, sustainable fishing